Genomic Structure of Hstx2 Modifier of Prdm9-Dependent Hybrid Male Sterility in Mice. Issue 3 (1st November 2019) - Lustyk, Diana; Kinský, Slavomír; Ullrich, Kristian Karsten; Yancoskie, Michelle; Kašíková, Lenka; Gergelits, Vaclav; Sedlacek, Radislav; Chan, Yingguang Frank; Odenthal-Hesse, Linda; Forejt, Jiri; Jansa, Petr
Abstract: F1 hybrids between mouse inbred strains PWD and C57BL/6 represent the most thoroughly genetically defined model of hybrid sterility in vertebrates. Hybrid male sterility can be fully reconstituted from three components of this model, the Prdm9 gene, intersubspecific homeology of Mus musculus musculus and Mus musculus domesticus autosomes, and the X-linked Hstx2 locus. Hstx2 modulates the extent of Prdm9 -dependent meiotic arrest and harbors two additional factors responsible for intersubspecific introgression-induced oligospermia ( Hstx1 ) and meiotic recombination rate ( Meir1 ). To facilitate positional cloning and to overcome the recombination suppression within the 4.3 Mb encompassing the Hstx2 locus, we designed Hstx2 -CRISPR and SPO11/Cas9 transgenes aimed to induce DNA double-strand breaks specifically within the Hstx2 locus. The resulting recombinant reduced the Hstx2 locus to 2.70 Mb (chromosome X: 66.51–69.21 Mb). The newly defined Hstx2 locus still operates as the major X-linked factor of the F1 hybrid sterility, and controls meiotic chromosome synapsis and meiotic recombination rate. Despite extensive further crosses, the 2.70 Mb Hstx2 interval behaved as a recombination cold spot with reduced PRDM9-mediated H3K4me3 hotspots and absence of DMC1-defined DNA double-strand-break hotspots. To search for structural anomalies as a possible cause of recombination suppression, we used optical mapping and observed high incidence of subspecies-specific structural variants along the X chromosome, with a striking copy number polymorphism of the microRNA Mir465 cluster. This observation together with the absence of a strong sterility phenotype in Fmr1 neighbor ( Fmr1nb ) null mutants support the role of microRNA as a likely candidate for Hstx2 .